Neuromania on the limits of brain science - Legrenzi, Paolo; q (Oxford : Oxford University Press, 2011)
Neuroeconomics, neuromarketing, neuroaesthetics and neurotheology are just a few of the novel disciplines that have been inspired by a combination of ancient knowledge along with recent discoveries about how the human brain works. This book critically questions our love affair with brain imaging.
Translated from the Spanish.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Neuropsychology